State modeling of the land mobile satellite channel by an image-based approach - Rieche, Marie; Arndt, Daniel; Ihlow, Alexander; Del Galdo, Giovanni (2013 7th European Conference on Antennas and Propagation, EuCAP 2013, 2013)
This contribution investigates the image-based characterization of the land mobile satellite (LMS) channel. For a comprehensive multi-satellite model, a traditional measurement-based approach is not feasible due to the lack of available satellites at all possible orbital positions. To overcome this challenge, we derive the LMS channel state-model from an evaluation of hemispheric images of the environment. With geometric considerations we can predict the position of an arbitrary satellite within the image. Based on this information the reception state of the LMS channel can be extracted. We determine the accuracy of the image-based method by comparing it with simultaneously recorded Radio Frequency (RF) signal levels and analyze it for various environments. © 2013 EurAAP.
CRIS-Team Scopus Importer:2025-11-10
Keywords: channel modeling; image processing; land mobile satellite channel; measurements; propagation